TINJAUAN PELAKSANAAN AUDIT ATAS AKUN KAS DAN SETARA KAS PT. ABC OLEH KAP BHARATA, ARIFIN, MUMAJAD & SAYUTI - Syahfa Dira Razilita (2023)
Cash and cash equivalents are one of the potentially material accounts for a company because they are liquid. Use of cash and cash equivalents PT. ABC also increase in 2022 and it is very possible that misstatements will occur in its financial statements. Therefore, it is mandatory to carry out an inspection in accordance with audit procedures. KAP Bharata, Arifin, Mumajad and Sayuti were asked to audit the financial statements of PT. ABC for financial reports as of December 31, 2022. This audit aims to find out whether the financial statements, especially cash and cash equivalent accounts, have been presented fairly or not by PT. ABC.